Glass structural member and electronic device
By providing alternately stacked refractive index material layers and diamond-like superhard layers containing doped elements on the surface of the glass structural parts, the problem of insufficient scratch resistance when high-hardness items are scratched is solved, and good scratch resistance and optical properties are achieved.
Patent Information
- Application Number
- CN202411582258.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Existing glass structural parts are difficult to maintain good scratch resistance when scratched by high-hardness items, and their optical permeability is also affected.
By providing a specific plating layer on the surface of the glass structural member, including alternately stacked layers of refractive index material and diamond-like superhard layer containing doped elements, its hardness and scratch resistance are improved while maintaining good optical transmissibility.
The glass structural parts are achieved for the long-lasting scratch resistance when scratched by high hardness items, while maintaining the optical properties of high transmittance and low chromatic aberration.
Smart Images

Figure CN119750918A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular to a glass structural component and an electronic device. Background Art
[0002] Glass is a common material for display screen covers in electronic devices such as mobile phones and tablets. In order to reduce scratches on the display screen, a superhard film (such as diamond-like carbon film) is usually coated on the surface of the glass substrate. In order not to affect the optical transmittance of the glass substrate, the thickness of the diamond-like carbon film is usually made thinner, but it is difficult to have a good scratch resistance effect on high-hardness sand particles. Therefore, it is necessary to provide a glass structure that can take into account both good scratch resistance and optical performance. Summary of the invention
[0003] In view of this, the embodiments of the present application provide a glass structure and an electronic device. By controlling a specific coating on the surface of the glass structure, it is possible to ensure that the glass structure has good scratch resistance and optical properties.
[0004] Specifically, a first aspect of an embodiment of the present application provides a glass structure, including:
[0005] Glass substrate,
[0006] A first optical scratch-resistant laminate is disposed on one side of the glass substrate; wherein the first optical scratch-resistant laminate comprises at least one layer of a first refractive index material layer and at least one layer of a second refractive index material layer alternately stacked, and the refractive index of the first refractive index material layer is greater than that of the second refractive index material layer;
[0007] A second optical scratch-resistant laminate is disposed on a side of the first optical scratch-resistant laminate away from the glass substrate; wherein the second optical scratch-resistant laminate comprises at least one layer of a third refractive index material layer, at least one layer of a fourth refractive index material layer, and at least one layer of a fifth refractive index material layer, and the refractive indices of the third refractive index material layer, the fourth refractive index material layer, and the fifth refractive index material layer decrease in sequence;
[0008] The first super-hard layer is arranged on the side of the second optical scratch-resistant layer away from the first optical scratch-resistant layer; wherein the first super-hard layer is diamond-like carbon containing doped elements, and the doped elements include at least one of silicon, aluminum, titanium, zirconium, molybdenum, tungsten, and nitrogen.
[0009] The above-mentioned glass structural member uses diamond-like carbon containing specific doping elements as the super-hard layer on the surface. Compared with the use of undoped diamond-like carbon as the super-hard layer, the surface hardness of the glass structural member is higher, and its scratch resistance can be improved. At the same time, the aforementioned doping elements can reduce the effect of the optical transmittance reduction caused by the undoped diamond-like carbon. In addition, a first optical scratch-resistant laminate composed of two overlapping film layers with different refractive indices and a second optical scratch-resistant laminate composed of three overlapping film layers with different refractive indices are arranged between the glass substrate and such a first super-hard layer. The thickness of each of these two optical laminates can be relatively thick and basically optically transparent, and both have good scratch resistance, among which the second optical scratch-resistant laminate has excellent scratch resistance. Their presence can effectively improve the long-lasting scratch resistance of the glass structural member with the first super-hard layer on the surface to high-hardness objects. Therefore, the glass structural member can take into account high hardness, good scratch resistance and optical properties (such as high transmittance and low color difference).
[0010] In the embodiment of the present application, the refractive index of the first refractive index material layer is greater than or equal to 1.8, and the refractive index of the second refractive index material layer is less than or equal to 1.60. By alternately stacking two material layers with refractive indices in these two ranges, a first optical scratch-resistant laminate with good optical transmittance and good scratch resistance can be obtained, and its optical transmittance is better.
[0011] In the embodiment of the present application, the refractive index of the third refractive index material layer is greater than 1.80, the refractive index of the fourth refractive index material layer is 1.60-1.80, and the refractive index of the fifth refractive index material layer is less than 1.60. By alternately stacking three material layers with refractive indices in these three ranges, a second optical scratch-resistant laminate with good optical transmittance and good scratch resistance can be obtained, and its scratch resistance is better.
[0012] In the embodiment of the present application, the first refractive index material layer includes one of a silicon nitride layer, an aluminum nitride layer, a silicon aluminum nitride layer, a silicon oxynitride layer, an aluminum oxynitride layer, and a silicon aluminum oxynitride layer; the second refractive index material layer includes one of a silicon oxide layer, an aluminum oxide layer, a silicon aluminum oxide layer, a silicon oxynitride layer, an aluminum oxynitride layer, and a silicon aluminum oxynitride layer. Among them, regulating the chemical composition of silicon oxynitride, aluminum oxynitride, and silicon aluminum oxynitride can achieve a refractive index within different ranges.
[0013] In the embodiment of the present application, the third refractive index material layer includes one of a silicon nitride layer, an aluminum nitride layer, a silicon aluminum nitride layer, and a titanium oxide layer; the fourth refractive index material layer includes one of a silicon oxynitride layer, an aluminum oxynitride layer, and a silicon aluminum oxynitride layer; the fifth refractive index material layer includes one of a silicon oxide layer, an aluminum oxide layer, and a silicon aluminum oxide layer. The refractive index of the materials selected for the third refractive index material layer is relatively high, and its wear resistance is good. By regulating the chemical composition of silicon oxynitride, aluminum oxynitride, and silicon aluminum oxynitride, its refractive index can be achieved between 1.60 and 1.80.
[0014] In some embodiments of the present application, the surface layer of the first optical scratch-resistant laminate close to the second optical scratch-resistant laminate is the first refractive index material layer, and the first refractive index material layer is in contact with the fourth refractive index material layer or the fifth refractive index material layer; or, the surface layer of the first optical scratch-resistant laminate close to the second optical scratch-resistant laminate is the second refractive index material layer, and the second refractive index material layer is in contact with the third refractive index material layer or the fourth refractive index material layer. This is conducive to the stacked structure of the first optical scratch-resistant laminate and the second optical scratch-resistant laminate having a higher optical transmittance as a whole.
[0015] In the embodiment of the present application, the sum of the thickness of the first optical scratch-resistant laminate and the second optical scratch-resistant laminate is in the range of 500nm-3000nm. In this case, the laminated structure formed by the first optical scratch-resistant laminate and the second optical scratch-resistant laminate can effectively improve the durable scratch resistance of the overall glass structure, and they can be firmly bonded to the glass substrate.
[0016] In the embodiment of the present application, the thickness of the first superhard layer is in the range of 1nm-100nm. The first superhard layer with a thickness below 100nm improves the surface hardness of one side of the glass structure without affecting its optical transmittance and appearance color.
[0017] In the embodiment of the present application, in the first superhard layer, the doping concentration of the doping element is less than or equal to 20wt%, so that the hardness and optical transmittance of the diamond-like material after doping can be improved without destroying the basic structure of the diamond-like material.
[0018] In some embodiments of the present application, a second superhard layer is further disposed on the side of the first superhard layer away from the second optical scratch-resistant laminate; the second superhard layer is made of a different material from the first superhard layer. The presence of the second superhard layer helps ensure that the first superhard layer has a long-lasting high hardness.
[0019] In the embodiment of the present application, the second superhard layer includes silicon nitride, silicon carbide, silicon carbonitride, CN x1One of the above; wherein x1 is between (0,4]. Providing a second super-hard layer of such a material between the first super-hard layer and the second optical scratch-resistant laminate can help improve the durability of the high hardness of the first super-hard layer, and with the cooperation of the two, improve the long-lasting scratch resistance of the surface layer of the glass structure to high-hardness objects.
[0020] In the embodiment of the present application, the thickness of the second superhard layer is in the range of 1nm-50nm. The second superhard layer with a suitable low thickness not only helps to improve the high hardness durability of the first superhard layer, but also has a high optical transmittance film layer and thus does not affect the appearance of the overall glass structure 100.
[0021] In some embodiments of the present application, the glass structure further includes an anti-fingerprint layer, which is located on the side of the second superhard layer away from the first superhard layer. The anti-fingerprint layer is mainly used to reduce the probability of a user's finger leaving dirt on the glass structure, ensuring a cleaner appearance of the glass structure.
[0022] In some other embodiments of the present application, the glass structure further includes an anti-fingerprint layer, which is located on the side of the first superhard layer away from the second optical scratch-resistant laminate. The anti-fingerprint layer is mainly used to reduce the probability of a user's finger leaving dirt on the glass structure, ensuring a clean appearance of the glass structure.
[0023] In the embodiment of the present application, the Mohs hardness of the surface of the glass structure away from the glass substrate is greater than or equal to 7. The surface of the glass structure away from the glass substrate has a higher Mohs hardness and better scratch resistance.
[0024] In the embodiment of the present application, the nanoindentation hardness of the glass structure away from the glass substrate is above 14 GPa at an indentation depth greater than 150 nm. The higher nanoindentation hardness reflects that the glass structure has better resistance to deep scratches or persistent scratches of high-hardness objects.
[0025] In the embodiment of the present application, the average transmittance of the glass structure in the visible light region is above 88%. After the film layer structure including the first optical scratch-resistant laminate, the second optical scratch-resistant laminate and the first superhard layer is arranged on one side of the glass substrate, the obtained glass structure can still have a high visible light transmittance, which is particularly suitable for display cover plates and camera protection cover plates with high transparency requirements.
[0026] In the embodiment of the present application, the color coordinate offset value ΔE of the glass structure compared to the glass substrate is less than 1.5, which indicates that the appearance color of the glass structure is not significantly changed compared with the untreated glass substrate.
[0027] A second aspect of an embodiment of the present application provides an electronic device, which includes a housing assembled on the outside of the electronic device and a circuit board located inside the housing, wherein the housing includes the glass structure described in the first aspect of the embodiment of the present application.
[0028] In some embodiments of the present application, the housing includes a display screen cover assembled on the front side of the electronic device; wherein the display screen cover adopts the glass structural member. In some other embodiments of the present application, the housing includes a back cover assembled on the back side of the electronic device; wherein the back cover adopts the glass structural member. In some further embodiments of the present application, the electronic device further includes a camera assembly located inside the housing, the housing includes a camera protection cover, the camera protection cover is covered on the camera assembly, and the camera protection cover adopts the glass structural member.
[0029] The above-mentioned glass structural parts can be used in one or more of the housings of the display cover, back cover, and camera protection cover of electronic devices. Since the above-mentioned glass structural parts have good wear resistance and scratch resistance, and the optical performance is not much different from that of the glass substrate, the housing of the electronic device using them is not easy to be scratched or worn during use, has a long service life, and has outstanding market competitiveness. Among them, the electronic devices can include but are not limited to mobile phones, tablet computers, laptops, wearable devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of the front structure of an electronic device provided in an embodiment of the present application.
[0031] Figure 2 A schematic diagram of the rear structure of an electronic device provided in an embodiment of the present application.
[0032] Figure 3a A schematic diagram of the structure of a glass structural member provided in an embodiment of the present application.
[0033] Figure 3b Another schematic diagram of the structure of the glass structure provided in the embodiment of the present application.
[0034] Figure 4 A schematic diagram of another structure of a glass structural member provided in some embodiments of the present application.
[0035] Figure 5 Another structural schematic diagram of a glass structural member provided for some other embodiments of the present application. DETAILED DESCRIPTION
[0036] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0037] See also Figure 1 and Figure 2 , Figure 1 A schematic diagram of the front structure of an electronic device provided in an embodiment of the present application. Figure 2 A schematic diagram of the rear structure of an electronic device provided in an embodiment of the present application. The electronic device 1000 may include, but is not limited to, a cell phone, a notebook computer, a tablet personal computer, a personal digital assistant, a wearable device (such as a smart bracelet, a watch, etc.), a virtual reality (VR) device, or a mobile device, etc. In the embodiment of the present application, the electronic device 1000 is an example of a mobile phone.
[0038] The electronic device 1000 includes a housing assembled on the outside of the electronic device, and a circuit board located inside the housing. The housing includes a display screen cover 101 assembled on the front side of the electronic device 1000 and a back cover 102 assembled on the back side of the electronic device 1000. The display screen cover 101 is covered on the display screen to protect it. The display screen cover 101 and / or the back cover 102 may be made of glass structural members. Specifically, the display screen cover 101 may be made of glass structural members in whole or in part; the back cover 102 may be made of glass structural members in whole or in part. The back cover 102 may cover only the back side (and the side away from the display screen) of the electronic device 1000, or may cover the back side and side frame of the electronic device 1000 at the same time. Optionally, the back cover 102 may cover all side frames around the electronic device, or may cover part of the side frames.
[0039] In some implementation modes of the present application, Figure 2 As shown, the electronic device 1000 also includes a camera assembly 2 located inside the housing, and the housing may include a camera protection cover 103, which is covered on the camera assembly 2 to protect the camera assembly 2. The camera protection cover 103 may be a glass structure. Similarly, the camera protection cover 103 may be partially or entirely a glass structure. The setting position of the camera protection cover 103 may be determined according to the setting position of the camera assembly 2, and it may be located on the front side of the electronic device 1000 or on the back side of the electronic device 1000. Figure 2In the example, the camera assembly 2 is located at the rear side of the electronic device 1000. In some embodiments of the present application, the camera protection cover plate 103 can be a separate structure from the display screen cover plate 101 or the back cover 102. In other embodiments of the present application, the camera protection cover plate 103 can also be an integrated structure with the display screen cover plate 101 or the back cover 102.
[0040] In the embodiment of the present application, the display screen cover 101, the back cover 102, and the camera protection cover 103 in the electronic device 1000 may be any one of the three using glass structural parts, any two of the three may be using glass structural parts, or all three may be using glass structural parts.
[0041] At present, in order to improve the scratch resistance of various components (such as display screen cover 101, camera protection cover 103) using glass in electronic device 1000, a layer of superhard film made of diamond-like material is usually plated on one side of the glass substrate. Taking the glass covered on the display screen and used as the display screen cover 101 as an example, a diamond-like film is usually plated on the side of the surface away from the display screen. The thickness of the diamond-like film is usually thin (less than 100nm, 3-50nm is more common), firstly because it is difficult to achieve thicker deposition of diamond-like, and secondly, if the thickness of the diamond-like film is made thicker, not only the manufacturing cost will increase dramatically, but also the light transmittance of the glass substrate will be greatly affected, affecting the appearance of the electronic device. To this end, the embodiment of the present application provides a glass structural member that has good wear resistance, scratch resistance, and optical transmittance to better meet the use requirements of the electronic device 1000.
[0042] The glass structural member provided in the embodiments of the present application is introduced below.
[0043] See also Figure 3a and Figure 3b , which are two exemplary structural schematic diagrams of glass structural members provided in the embodiments of the present application. Figure 3a and Figure 3b As shown, the glass structure 100 includes a glass substrate 10 and a first optical scratch-resistant laminate 11, a second optical scratch-resistant laminate 12, and a first superhard layer 13 which are sequentially stacked on one side of the glass substrate 10. Specifically, the first optical scratch-resistant laminate 11 is disposed on one side of the glass substrate 10, the second optical scratch-resistant laminate 12 is disposed on a side of the first optical scratch-resistant laminate 11 away from the glass substrate 10, and the first superhard layer 13 is disposed on a side of the second optical scratch-resistant laminate 12 away from the first optical scratch-resistant laminate 11.
[0044] Among them, the first optical scratch-resistant layer 11 includes at least one layer of first refractive index material layer 111 and at least one layer of second refractive index material layer 112 alternately stacked, and the refractive indexes of the first refractive index material layer 111 and the second refractive index material layer 112 are different. For example, the refractive index of the first refractive index material layer 111 is greater than the refractive index of the second refractive index material layer 112.
[0045] The second optical scratch-resistant laminate 12 includes at least one layer of a third refractive index material layer 121, at least one layer of a fourth refractive index material layer 122, and at least one layer of a fifth refractive index material layer 123, which are stacked. The refractive indices of these three material layers are different. For example, the refractive indices of the third refractive index material layer 121, the fourth refractive index material layer 122, and the fifth refractive index material layer 123 decrease in sequence.
[0046] The first superhard layer 13 is diamond-like carbon containing doping elements, wherein the doping elements include at least one of silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), molybdenum (Mo), tungsten (W), and nitrogen (N).
[0047] In the present application, a first optical scratch-resistant layer 11 formed by overlapping two material layers with different refractive indices, a second optical scratch-resistant layer 12 formed by overlapping three material layers with different refractive indices, and a first superhard layer 13 composed of diamond-like carbon containing specific doping elements are sequentially stacked on a glass substrate 10. Firstly, at least one doping element among Si, Al, Ti, Zr, Mo, and N contained in the diamond-like carbon can be doped and modified to help improve its hardness, enhance the wear resistance of the glass structural component 100 and its resistance to scratches on daily necessities (such as keys, etc.). At the same time, compared with an undoped diamond-like carbon layer, the diamond-like carbon layer doped with the aforementioned elements has a higher optical transmittance at the same thickness, that is, the aforementioned doping elements reduce the damage to the optical performance. Secondly, the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 are arranged between the glass substrate 10 and the first superhard layer 13. The thickness of the two optical laminates can be made thicker and maintain good optical transmittance, and both have good wear resistance and scratch resistance. In cooperation with the first superhard layer 13, the nanoindentation hardness of the glass structure 100 can be improved, and its long-lasting scratch resistance to high-hardness objects (such as sand / dust with a Mohs hardness of more than 7) can be enhanced. Even if the thickness of the first superhard layer 13 of the glass structure 100 becomes thinner after long-term use, the presence of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 can still ensure that the glass structure 100 has good scratch resistance. Therefore, the glass structure 100 can have higher hardness, good scratch resistance and scratch resistance, and its optical properties such as light transmittance and appearance color are not significantly changed compared with the glass substrate 10.
[0048] It should be noted that Figure 3a and Figure 3b The figures are for illustrative purposes only and do not represent the actual size of the product. The thickness of each film layer and the thickness ratio between each film layer in the figure are not intended to limit the actual product of the present application; the same interpretation shall apply to other figures in the present application. In addition, Figure 3a , Figure 3b Only one film arrangement form of the first optical scratch-resistant laminate 11 and one film arrangement form of the second optical scratch-resistant laminate 12 are illustrated respectively, but this does not mean that the actual film arrangement form of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 is limited to the present application. Figure 3a , Figure 3b As shown.
[0049] Specifically, if the first refractive index material layer 111 is recorded as layer A and the second refractive index material layer 112 is recorded as layer C, then in the first optical scratch-resistant laminate 11, the total number of layers A and the total number of layers B may be equal or different. For example, in the direction from the glass substrate 10 to the first optical scratch-resistant laminate 11 (i.e., Figure 3a , Figure 3b The Z direction indicated by the arrow in the middle), the film layer arrangement of the first optical scratch-resistant laminate 11 can be (AC) n (like Figure 3a shown), or (AC) n -A, or (CA) n (like Figure 3b shown), or (CA) n -C; where n is an integer greater than or equal to 1. The thickness of each A layer can be the same or different. The thickness of each C layer can be the same or different. Where, “-” represents a stacking relationship, for example (AC) n The stacking in sequence along the Z direction is represented by A layer, C layer, ..., A layer and C layer; wherein the total number of cycles of A layer stacking C layer is n times. By alternately stacking two material layers with different refractive indices, a first optical scratch-resistant stacked layer 11 with good optical transmittance and good scratch resistance can be obtained, and its optical transmittance is better.
[0050] In the second optical scratch-resistant laminate 12, the arrangement of the third refractive index material layer 121, the fourth refractive index material layer 122, and the fifth refractive index material layer 123 is not limited, as long as the two contacting film layers are material layers with different refractive indices. If the third refractive index material layer 121 is recorded as the D layer, the fourth refractive index material layer 122 is recorded as the E layer, and the fifth refractive index material layer 123 is recorded as the F layer, that is, there is an E layer or an F layer between adjacent D layers, there is a D layer or an F layer between adjacent E layers, and there is a D layer or an E layer between adjacent F layers. Exemplarily, along the Z direction, the film layer arrangement of the second optical scratch-resistant laminate 12 can include, but is not limited to, (DEF) n (like Figure 3ashown), (DEF) n -A, (DEF) n -DE, (FED) n , (FED) n -F, (FED) n -FE、(EFD) n -FE, or (DE) m -(DEF) n etc. m and n are integers greater than or equal to 1. Similar to the above paragraph, “-” represents the stacking relationship along the Z direction. By stacking three materials with different refractive indices, a second optical scratch-resistant laminate 12 with good optical transmittance and good scratch resistance can be obtained, and its scratch resistance is better.
[0051] In the present application, the laminated structure composed of the first optical scratch-resistant laminated layer 11 and the second optical scratch-resistant laminated layer 12 has a transmittance of greater than or equal to 90% for visible light. The laminated structure has high optical transparency (for example, an average transmittance of visible light is greater than 90%), and being arranged between the glass substrate 10 and the first superhard layer 13 will not affect the visible light transmittance of the overall glass structural member 100. Among them, the first optical scratch-resistant laminated layer 11 is an optically transparent layer, and the second optical scratch-resistant laminated layer 12 is an optically transparent layer.
[0052] In the embodiment of the present application, in the first optical scratch-resistant laminate 11, the refractive index of the first refractive index material layer 111 (the aforementioned A layer) is greater than or equal to 1.80, and the refractive index of the second refractive index material layer 112 (the aforementioned C layer) is less than or equal to 1.60. By alternately stacking two different refractive index material layers whose refractive indices are respectively in these ranges, a first optical scratch-resistant laminate 11 having good optical transmittance and good scratch resistance can be obtained, and its optical transmittance is better. In some embodiments of the present application, the refractive index of layer A is greater than or equal to 1.80, and the refractive index of layer C is less than 1.60; or, the refractive index of layer A is greater than 1.80, and the refractive index of layer C is less than or equal to 1.60; or, the refractive index of layer A is greater than 1.80, and the refractive index of layer C is less than 1.60. In some embodiments, the refractive index of layer A is greater than or equal to 1.85, and the refractive index of layer C is less than or equal to 1.55.
[0053] The first refractive index material layer 111 may include a silicon nitride layer (ie, a Si3N4 layer), an aluminum nitride layer (ie, an AlN layer), a silicon aluminum nitride layer (ie, a Si w Al z N x ), silicon oxynitride layer (Si w O y N x ), aluminum nitride layer (Al z O y Nx ), silicon aluminum oxynitride layer (Si w Al z O y N x ). The second refractive index material layer 112 may include a silicon oxide layer (such as a SiO2 layer), an aluminum oxide layer (i.e., an Al2O3 layer), a silicon aluminum oxide layer (Si w Al z O y ), silicon oxynitride layer (Si w O y N x ), aluminum nitride layer (Al z O y N x ), silicon aluminum oxynitride layer (Si w Al z O y N x )
[0054] It should be noted that the subscripts of the elements in the above chemical formulas should be such that the corresponding chemical formulas satisfy charge balance. In addition, the x in the above chemical formulas do not have an associated relationship, the y in the chemical formulas do not have an associated relationship, the z in the chemical formulas do not have an associated relationship, and the w in the chemical formulas do not have an associated relationship. The same letters (such as z, w, etc.) in different chemical formulas do not have an associated relationship, but are not distinguished for the convenience of expression.
[0055] Among them, although the material selection ranges of the first refractive index material layer 111 and the second refractive index material layer 112 both mention silicon oxynitride, aluminum oxynitride, and silicon aluminum oxynitride, since the refractive indices of these two material layers are in different ranges, even if they are both silicon oxynitride (taking this as an example), the chemical formula of silicon oxynitride in the first refractive index material layer 111 is not the same as the chemical formula of silicon oxynitride in the second refractive index material layer 112.
[0056] In some embodiments of the present application, the first refractive index material layer 111 is selected from one of a silicon nitride layer, an aluminum nitride layer, and a silicon aluminum nitride layer; the second refractive index material layer 112 is selected from one of a silicon oxide layer, an aluminum oxide layer, and a silicon aluminum oxide layer. In one embodiment, the first refractive index material layer 111 is a silicon aluminum nitride layer, and the second refractive index material layer 112 is a silicon aluminum oxide layer. In this case, while meeting the above refractive index requirements of the present application, the interlayer bonding force between the first refractive index material layer 111 and the second refractive index material layer 112 is relatively high.
[0057] In the embodiment of the present application, the refractive index of the third refractive index material layer 121 (the aforementioned D layer) is greater than 1.80, the refractive index of the fourth refractive index material layer 122 (the aforementioned E layer) is 1.60-1.80 (i.e. greater than or equal to 1.60 to less than or equal to 1.80), and the refractive index of the fifth refractive index material layer 123 (the aforementioned F layer) is less than 1.60. By stacking three different refractive index material layers with refractive indices in these ranges, a second optical scratch-resistant laminate 12 with good optical transmittance and good scratch resistance can be obtained, and its scratch resistance is better. In some embodiments of the present application, the refractive index of the D layer is greater than or equal to 1.85, the refractive index of the F layer is less than or equal to 1.55, and the refractive index of the E layer is in the range of 1.60-1.80.
[0058] It should be noted that the refractive indexes of layer A, layer C, layer D, layer E, and layer F in this application may have reasonable errors within a certain range due to the influence of the testing method, and the above data within the reasonable error range should also be regarded as within the scope of protection of this application. Other parameter ranges mentioned below in this application should also be interpreted similarly.
[0059] The third refractive index material layer 121 may include a silicon nitride layer (ie, a Si3N4 layer), an aluminum nitride layer (ie, an AlN layer), a silicon aluminum nitride layer (ie, a Si w Al z N x ), a titanium oxide layer (such as a TiO2 layer). These materials have high hardness and good scratch resistance. The fourth refractive index material layer 122 includes a silicon nitride layer (Si w O y N x ), aluminum nitride layer (Al z O y N x ), silicon aluminum oxynitride layer (Si w Al z O y N x The fifth refractive index material layer 123 includes a silicon oxide layer (such as a SiO2 layer), an aluminum oxide layer (i.e., an Al2O3 layer), a silicon aluminum oxide layer (Si w Al z O y )
[0060] Similarly, although the material selection range of the fourth refractive index material layer 122 mentions silicon oxynitride, aluminum oxynitride, and silicon aluminum oxynitride, which are the same as the first refractive index material layer 111 and the second refractive index material layer 112, based on the refractive indices of these three film layers being in different ranges, even if they are made of the same material (for example, all are silicon oxynitride), the chemical formulas of the silicon oxynitride in these three film layers are not the same.
[0061] In the present application, the above-mentioned A layer, C layer, D layer, E layer, and F layer can be independently plated by chemical vapor deposition or physical vapor deposition, wherein chemical vapor deposition includes but is not limited to hot wire chemical vapor deposition or plasma enhanced chemical vapor deposition, etc. Physical vapor deposition includes but is not limited to magnetron sputtering, vacuum evaporation, ion plating (such as arc ion plating, radio frequency ion plating), etc.
[0062] For example, when a silicon oxynitride layer is formed by a magnetron sputtering process, the target material used may be a Si target, and an inert gas (such as argon), nitrogen (N2) and oxygen (O2) are introduced to deposit and form the silicon oxynitride layer. The Si oxynitride layer can be regulated by adjusting the flow rates of N2 and O2. w O y N x When the silicon aluminum nitride layer is formed by magnetron sputtering, the target materials used include Si target and Al target, and argon and N2 are introduced to deposit and form the silicon aluminum nitride layer. The Si aluminum nitride layer can be adjusted by adjusting the sputtering power and time of the Si target and the Al target. w Al z N x When the silicon aluminum oxynitride layer is formed by magnetron sputtering, the target materials used include Si target and Al target, and argon, N2 and O2 are introduced to deposit the target coating.
[0063] In some embodiments of the present application, when the surface layer of the first optical scratch-resistant laminate 11 close to the second optical scratch-resistant laminate 12 is a second refractive index material layer 112 (eg Figure 3a As shown in FIG. 1 , the second refractive index material layer 112 is in contact with the third refractive index material layer 121 or the fourth refractive index material layer 122 in the second optical scratch-resistant laminate 12. This is conducive to the stacked structure of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 having higher optical transmittance. In this case, the film layer arrangement of the first optical scratch-resistant laminate 11 along the Z direction can be (AC) n (like Figure 3a shown), or (CA) n -C. Figure 3a In the figure, the second refractive index material layer 112 is shown to be in contact with the third refractive index material layer 121 .
[0064] In some other embodiments of the present application, when the surface layer of the first optical scratch-resistant laminate 11 close to the second optical scratch-resistant laminate 12 is a first refractive index material layer 111 (eg Figure 3bAs shown in FIG. 1 , the first refractive index material layer 111 is in contact with the fourth refractive index material layer 122 or the fifth refractive index material layer 123 in the second optical scratch-resistant laminate 12. This is conducive to the laminated structure of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 having higher optical transmittance. In this case, the film layer arrangement of the first optical scratch-resistant laminate 11 along the Z direction can be (CA) n (like Figure 3b shown), (AC) n -A. Figure 3b In the figure, the first refractive index material layer 111 is shown to be in contact with the fourth refractive index material layer 122 .
[0065] In the present application, the number of film layers included in the first optical scratch-resistant laminate 11 is greater than or equal to 2, and further greater than or equal to 3. When the number of film layers of the first optical scratch-resistant laminate 11 is greater than or equal to 3, the number of layers of the first refractive index material layer 111 and / or the second refractive index material layer 112 is greater than or equal to 2. Among them, the number of film layers included in the second optical scratch-resistant laminate 12 is greater than or equal to 3, and further greater than or equal to 4.
[0066] In the embodiment of the present application, the total number of film layers included in the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 is greater than or equal to 5 layers, and can further be in the range of 8-30 layers, for example, specifically 10 layers, 12 layers, 15 layers, 20 layers, 25 layers or 28 layers, etc. In this way, the stacking structure of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 can be endowed with good optical transmittance and scratch resistance by stacking a suitable number of material layers with different refractive indices, and ensure that they are firmly bonded to the glass substrate 10.
[0067] In the present application, the thickness of the first refractive index material layer 111 (A layer), the second refractive index material layer 112 (C layer), the third refractive index material layer 121 (D layer), the fourth refractive index material layer 122 (E layer), and the fifth refractive index material layer 123 (F layer) is not particularly limited. In a common embodiment of the present application, the thickness of each A layer, C layer, D layer, E layer, and F layer can be independently within the range of 1-2500nm, and can further be within the range of 5nm-2000nm.
[0068] In the present application, the thickness of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 are both greater than the thickness of the first superhard layer 13. Disposing them under the first superhard layer 13 can help the overall glass structure 100 to resist scratches from high-hardness objects for a long time.
[0069] In a possible implementation of the present application, the sum of the thicknesses of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 may be in the range of 500nm-3000nm. In this case, the laminated structure formed by the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 can be firmly bonded to the glass substrate 10, while being sufficient to improve the durable wear resistance and durable scratch resistance of the overall glass structure 100. Exemplarily, the sum of the thicknesses may be 600nm, 800nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, 2200nm, or 2400nm, etc. In some implementations, the sum of the thicknesses of the first optical scratch-resistant laminate 11 and the second optical scratch-resistant laminate 12 is 1000nm-2500nm.
[0070] In the present application, in the first superhard layer 13, the doping elements in the diamond-like carbon include one or more of silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), molybdenum (Mo), tungsten (W), and nitrogen (N). For example, the doping elements in the diamond-like carbon include N; or include Si; or include Al; or include Ti; or include Zr; or include Mo; or include W; or include Si and Ti; or include Ti and Al; or include Mo and W; or include Si and N, etc. The Mohs hardness of the diamond-like carbon doped with these elements can reach above 8 and the optical properties are also good, and it is relatively easy to prepare.
[0071] In some embodiments of the present application, in the first superhard layer 13, the doping element in the diamond-like carbon may further include hydrogen (H) element. The doping element H may also help to improve the hardness of the diamond-like carbon.
[0072] In some embodiments of the present application, the first superhard layer 13 is one of a Si-doped diamond-like layer, an Al-doped diamond-like layer, a Ti-doped diamond-like layer, a Zr-doped diamond-like layer, a Mo-doped diamond-like layer, a W-doped diamond-like layer, and a N-doped diamond-like layer. These doped diamond-like layers are easier to prepare and can better balance high hardness and good optical transmittance.
[0073] In a possible implementation manner of the present application, in the first superhard layer 13, the doping concentration of the doping element is less than or equal to 20wt%. This ensures that the introduction of the doping element will not destroy the structural stability of the diamond-like carbon, while ensuring the high hardness and good optical transmittance of the diamond-like carbon layer after doping. It should be noted that the concentration of the doping element mentioned here specifically refers to the sum of the doping concentrations of all doping elements in the first superhard layer 13. In the present application, the diamond-like carbon containing the doping element can be plated by physical vapor deposition (such as magnetron sputtering) or chemical vapor deposition (such as plasma enhanced chemical vapor deposition).
[0074] In the embodiment of the present application, the thickness of the first superhard layer 13 is within the range of 1nm-100nm. The thickness of the first superhard layer 13 is below 100nm, and it can ensure that it is a film layer with higher transparency while improving the surface hardness of one side of the glass structure 100, and ensure that the optical transmittance and appearance effect of the overall glass structure 100 are not much different from those of the simple glass substrate 10. Specifically, the thickness of the first superhard layer 13 can be 2nm, 3nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, or 95nm. In some embodiments, the thickness of the first superhard layer 13 is within the range of 3nm-50nm, and can further be within the range of 2nm-30nm. In this case, the surface hardness of the glass structure 100 with the first super-hard layer 13 is higher and has longer scratch resistance, and the first super-hard layer 13 can have higher optical transmittance.
[0075] Figure 4 This is another structural schematic diagram of a glass structural member provided in some embodiments of the present application. Figure 4 Compare Figure 3a The second superhard layer 14 and the anti-fingerprint layer 15 described below are additionally provided.
[0076] like Figure 4 As shown, the second superhard layer 14 is disposed on the side of the first superhard layer 13 away from the second optical scratch-resistant laminate 12. The second superhard layer 14 is made of a different material from the first superhard layer 13. The second superhard layer 14 can help the first superhard layer 13 have a longer-lasting high hardness, and with the cooperation of the two, the surface layer of the glass structure 100 is improved to have a long-lasting scratch resistance to high-hardness objects. The second superhard layer 14 may include silicon nitride (Si3N4), silicon carbide (SiC), silicon carbonitride (SiN x2 C y2 ), CN x1 One of them. Among them, x1, x2, y2 are all between (0,4].
[0077] In the embodiment of the present application, the thickness of the second superhard layer 14 is in the range of 1nm-50nm. The optical transmittance of the second superhard layer 14 with a suitable low thickness will not be too low to affect the appearance of the overall glass structure 100. Specifically, the thickness of the second superhard layer 14 can be 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm or 45nm. In some embodiments, the thickness of the second superhard layer 14 is in the range of 2nm-20nm.
[0078] In some embodiments, Figure 4 As shown, the glass structure 100 further includes an anti-fingerprint layer (Anti-fingerprint film, referred to as AF layer) 15, which is located on the side of the second superhard layer 14 away from the first superhard layer 13. The anti-fingerprint layer 15 is mainly used to reduce the formation of fingerprints on the glass structure 100 when the user's finger touches it, so as not to affect the appearance of the glass structure 100. In addition, the second superhard layer 14 is arranged between the anti-fingerprint layer 15 and the first superhard layer 13, which can reduce the effect of the base layer of the anti-fingerprint layer 15 on the hardness degradation of the first superhard layer 13 during long-term use.
[0079] Generally, the material of the AF layer 15 includes fluorine-containing compounds and / or silicon-containing compounds. These two types of compounds have hydrophobic and oleophobic properties, making the surface of the glass structural member 100 easy to clean and having good anti-fingerprint residue ability. In some embodiments, the thickness of the anti-fingerprint layer 15 can be in the range of 5nm-50nm. The anti-fingerprint layer 15 of appropriate thickness is beneficial to the glass structural member 100 having good anti-fingerprint durability and wear resistance, and will not significantly affect its optical transmittance.
[0080] Figure 5 This is another structural schematic diagram of a glass structural member provided in some other embodiments of the present application. Figure 5 Compare Figure 3a The anti-fingerprint layer 15 described below is additionally provided.
[0081] In some implementation modes of the present application, Figure 5 As shown, the glass structure 100 further includes an anti-fingerprint layer 15, which is located on the side of the first superhard layer 13 away from the second optical scratch-resistant laminate 12. The function, thickness, material, etc. of the anti-fingerprint layer 15 can be found in the previous description of this application and will not be repeated here.
[0082] It should be noted that, in the absence of conflict, the various features in the various embodiments of the present application can be combined with each other, and any combination of features in different embodiments is also within the protection scope of the present application, that is, the multiple embodiments described above can also be combined arbitrarily according to actual needs. Figure 3b In the glass structure 100 shown, an AF layer 15 is also provided on the side of the first superhard layer 13 away from the second optical scratch-resistant laminate 12. Further, a second superhard layer 14 may be provided between the AF layer 15 and the first superhard layer 13. In addition, the glass structure 100 of the embodiment of the present application may also be flexibly provided with other film layer structures according to actual needs.
[0083] In the embodiment of the present application, the Mohs hardness of the surface of each glass structural member 100 away from the glass substrate 10 is greater than or equal to 7. The term "Mohs hardness" is also called scratch hardness, which is measured by scratching the surface of the glass structural member 100 away from the glass substrate 10 using a mineral with known hardness based on the scratch method. The Mohs hardness is not an absolute hardness value, but a relative hardness expressed in the order of hardness.
[0084] The Mohs hardness of the surface of the glass structure 100 on the side away from the glass substrate 10 is greater than or equal to 7. When the surface is scratched by an object with a hardness not exceeding 7, the first super-hard layer 13 with a relatively large hardness mainly resists the external scratching force, and the surface of the glass structure 100 is basically free of scratches. When the surface is scratched by an object with a hardness greater than 7, the first super-hard layer 13 and the second optical scratch-resistant laminate 12 and the first optical scratch-resistant laminate 11 with a relatively large thickness cooperate to better resist scratches caused by high-hardness objects.
[0085] It should be noted that when testing the Mohs hardness, a mineral with known hardness is used to scratch the exposed surface of the glass structure 100 away from the glass substrate 10 (that is, the surface of the layer farthest from the glass substrate 10). Figure 3a and Figure 3b For the glass structure 100 shown in FIG. 1 , the first superhard layer 13 is specifically scratched; Figure 4 and Figure 5 For the scratching of the glass structure 100 shown, the anti-fingerprint layer 15 thereof is specifically scratched.
[0086] In the embodiment of the present application, the nanoindentation hardness of each of the glass structural members 100 on the side away from the glass substrate 10 at an indentation depth of more than 150 nm is above 14 GPa. The nanoindentation hardness of the glass structural member 100 is relatively high, reflecting that it can better resist deep scratches or lasting scratches caused by high-hardness objects. Among them, the test method of the nanoindentation hardness includes: pressing a diamond indenter on the exposed surface of the glass structural member 100 on the side away from the glass substrate 10, and then gradually pressing the indenter under an increasing external load until a predetermined indentation depth is reached, and the indentation hardness can be calculated by measuring the indentation depth and the corresponding external load at this time. It should be noted that during the test process, in the initial stage, as the external load increases, the indentation depth will gradually increase, and in the later stage, when the external load increases again, the indentation depth will basically not change.
[0087] In the embodiment of the present application, the average transmittance of each of the above-mentioned glass structural members 100 in the visible light region (specifically, the wavelength is 400nm-700nm) is above 88%. After a film layer structure including at least the first optical scratch-resistant laminate 11, the second optical scratch-resistant laminate 12 and the first superhard layer 13 is arranged on one side of the glass substrate 10, the obtained glass structural member 100 can still have a relatively high visible light transmittance, and is particularly suitable for display screen cover 101, camera protection cover 103 and the like that have high requirements for transparency.
[0088] In the embodiment of the present application, the color coordinate offset value ΔE of each of the glass structural members 100 compared to the glass substrate 10 is less than 1.5. The color coordinate offset value ΔE can reflect the degree of color change of each of the glass structural members 100 compared to the glass substrate 10. ΔE=[(ΔL) 2 +(Δa) 2 +(Δb) 2 ] 1 / 2 ; ΔL represents the difference in L value between the glass structural member 100 and the glass substrate 10 in the Lab chromaticity coordinates, Δa represents the difference in a value between the glass structural member 100 and the glass substrate 10 in the Lab chromaticity coordinates, and Δb represents the difference in b value between the glass structural member 100 and the glass substrate 10 in the Lab chromaticity coordinates. Among them, the larger the ΔE value, the greater the color difference of the glass structural member 100 compared with the glass substrate 10. The above-mentioned smaller ΔE value indicates that after the film layer structure including at least the aforementioned first optical scratch-resistant laminate 11, the second optical scratch-resistant laminate 12 and the first superhard layer 13 is provided on one side of the glass substrate 10, the obtained glass structural member 100 still has a low colorability and the appearance effect is basically not affected.
[0089] The above-mentioned glass structural member 100 provided in the embodiment of the present application, by sequentially arranging the film structure including the above-mentioned first optical scratch-resistant laminate 11, the second optical scratch-resistant laminate 12 and the first superhard layer 13 on the surface of one side of the glass substrate, can make the glass structural member have high hardness, good wear resistance, scratch resistance, while its optical performance is not much different from that of the simple glass substrate 10, so that the glass component can better meet the various use requirements and use experience of electronic equipment, and has high quality reliability. In addition, the glass structural member 100 of the embodiment of the present application is compared with the glass substrate having only an undoped corundum layer (the thickness is the same as the first superhard layer 13 of the present application) on the surface, and its nanoindentation hardness at the same indentation depth greater than 150nm is higher, and the durability of deep scratch resistance is better. In addition, when the glass structural member 100 of the embodiment of the present application includes the above-mentioned second superhard layer 14, its nanoindentation hardness can be greater and the scratch resistance is higher.
[0090] The embodiment of the present application also provides an electronic device using the above glass structure. As described above, in the electronic device 1000, at least one of the display cover 101, the back cover 102, and the camera protection cover 103 can use the glass structure 100 provided in the embodiment of the present application.
[0091] For example, when the display screen cover plate 101 adopts the above-mentioned glass structure 100, the glass substrate 10 of the glass structure 100 is close to the display screen. The user touches the side surface of the glass structure 100 away from the glass substrate 10. The display screen cover plate 101 is used to cover the display screen, which can reduce the scratches and wear of the display screen during the use of the electronic device without affecting the display effect.
[0092] For example, when the camera protection cover 103 adopts the above-mentioned glass structure 100, the glass substrate 10 of the glass structure 100 is close to the camera assembly 2, and the first superhard layer 13 is far away from the camera assembly 2. The camera protection cover 103 is used to cover the camera assembly 2, which can reduce the scratches and wear of the camera of the camera assembly 2 during the use of the electronic device without affecting the camera effect.
[0093] The above only expresses the exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.
[0094] It should be noted that all the above drawings are illustrative illustrations of the present application and do not represent the actual size of the product. Moreover, the size ratio relationship between the components in the drawings is not intended to limit the actual product of the present application.
[0095] The terms "first", "second", "third", and "fourth" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", "third", and "fourth" may explicitly or implicitly include one or more of the features.
[0096] In the description of this application, unless otherwise specified, the meaning of "multiple (kinds)" refers to greater than or equal to two (kinds). "At least one (kind)" refers to one (kind) or more (kinds). "At least one of the following (kinds)" or similar expressions refers to any combination of these items, including any combination of single (kinds) or plural (kinds). For example, "at least one (kind) of a, b, or c", or "at least one (kind) of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.
[0097] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0098] In addition, the numerical range represented by "-" in the present application refers to the range in which the numerical values recorded before and after "-" are included as the minimum and maximum values, respectively. Expressions about parameter ranges in the present application, such as "greater than or equal to (≥)", "less than or equal to (≤)", "above...", "below..." all include this number. The various numerical values and numerical ranges involved in the embodiments of the present application are approximate values, and may have a certain range of errors due to the influence of manufacturing processes / test methods, etc. The above-mentioned various numerical values and numerical ranges are also deemed to be within the scope of protection of the present application when they are within the reasonable error range of measurement.
Claims
1. A glass structural member (100), characterized in that: include: A glass substrate (10), A first optical scratch-resistant laminate (11) is arranged on one side of the glass substrate (10); wherein the first optical scratch-resistant laminate (11) comprises at least one first refractive index material layer (111) and at least one second refractive index material layer (112) alternately stacked, and the refractive index of the first refractive index material layer (111) is greater than that of the second refractive index material layer (112); A second optical scratch-resistant laminate (12) is arranged on a side of the first optical scratch-resistant laminate (11) away from the glass substrate (10); wherein the second optical scratch-resistant laminate (12) comprises at least one layer of a third refractive index material layer (121), at least one layer of a fourth refractive index material layer (122), and at least one layer of a fifth refractive index material layer (123) which are stacked, and the refractive indices of the third refractive index material layer (121), the fourth refractive index material layer (122), and the fifth refractive index material layer (123) decrease in sequence; A first superhard layer (13) is arranged on a side of the second optical scratch-resistant laminate (12) away from the first optical scratch-resistant laminate (11); wherein the first superhard layer (13) is diamond-like carbon containing doped elements, and the doped elements include at least one of silicon, aluminum, titanium, zirconium, molybdenum, tungsten, and nitrogen.
2. The glass structural member according to claim 1, characterized in that: The refractive index of the first refractive index material layer (111) is greater than or equal to 1.8, and the refractive index of the second refractive index material layer (112) is less than or equal to 1.60; The refractive index of the third refractive index material layer (121) is greater than 1.80, the refractive index of the fourth refractive index material layer (122) is 1.60-1.80, and the refractive index of the fifth refractive index material layer (123) is less than 1.
60.
3. The glass structural member according to claim 2, characterized in that: The first refractive index material layer (111) comprises one of a silicon nitride layer, an aluminum nitride layer, a silicon aluminum nitride layer, a silicon oxynitride layer, an aluminum oxynitride layer, and a silicon aluminum oxynitride layer; The second refractive index material layer (112) comprises one of a silicon oxide layer, an aluminum oxide layer, a silicon aluminum oxide layer, a silicon oxynitride layer, an aluminum oxynitride layer, and a silicon aluminum oxynitride layer.
4. The glass structural member according to claim 2, characterized in that: The third refractive index material layer (121) comprises one of a silicon nitride layer, an aluminum nitride layer, a silicon aluminum nitride layer, and a titanium oxide layer; The fourth refractive index material layer (122) comprises one of a silicon oxynitride layer, an aluminum oxynitride layer, and a silicon aluminum oxynitride layer; The fifth refractive index material layer (123) comprises one of a silicon oxide layer, an aluminum oxide layer, and a silicon aluminum oxide layer.
5. The glass structural member according to any one of claims 1 to 4, characterized in that: The surface layer of the first optical scratch-resistant laminate (11) close to the second optical scratch-resistant laminate (12) is the first refractive index material layer (111), and the first refractive index material layer (111) is in contact with the fourth refractive index material layer (122) or the fifth refractive index material layer (123); Alternatively, the surface layer of the first optical scratch-resistant laminate (11) close to the second optical scratch-resistant laminate (12) is the second refractive index material layer (112), and the second refractive index material layer (112) is in contact with the third refractive index material layer (121) or the fourth refractive index material layer (122).
6. The glass structural member according to any one of claims 1 to 5, characterized in that: The thicknesses of the first refractive index material layer (111), the third refractive index material layer (121), the fourth refractive index material layer (122) and the fifth refractive index material layer (123) are respectively in the range of 1 nm-2500 nm.
7. The glass structural member according to any one of claims 1 to 6, characterized in that: The sum of the thicknesses of the first optical scratch-resistant laminate (11) and the second optical scratch-resistant laminate (12) is in the range of 500 nm to 3000 nm.
8. The glass structural member according to any one of claims 1 to 7, characterized in that: The thickness of the first superhard layer (13) is in the range of 1 nm to 100 nm.
9. The glass structural member according to any one of claims 1 to 8, characterized in that: In the first superhard layer (13), the doping concentration of the doping element is less than or equal to 20 wt%.
10. The glass structural member according to any one of claims 1 to 9, characterized in that: A second superhard layer (14) is also provided on the side of the first superhard layer (13) facing away from the second optical scratch-resistant laminate (12); the second superhard layer (14) and the first superhard layer (13) are made of different materials.
11. The glass structural member according to claim 10, characterized in that: The second superhard layer (14) comprises silicon nitride, silicon carbide, silicon carbonitride, CN x1 One of the following; where x1 is between (0,4].
12. The glass structural member according to claim 10 or 11, characterized in that: The thickness of the second superhard layer (14) is in the range of 1 nm to 50 nm.
13. The glass structural member according to any one of claims 10 to 12, characterized in that: The glass structural member (100) further comprises an anti-fingerprint layer (15), wherein the anti-fingerprint layer (15) is located on a side of the second superhard layer (14) facing away from the first superhard layer (13).
14. The glass structural member according to any one of claims 1 to 9, characterized in that: The glass structure (100) further comprises an anti-fingerprint layer (15), wherein the anti-fingerprint layer (15) is located on a side of the first superhard layer (13) that is away from the second optical scratch-resistant laminate (12).
15. The glass structural member according to any one of claims 1 to 14, characterized in that: The Mohs hardness of a surface of the glass structure (100) on a side away from the glass substrate (10) is greater than or equal to 7.
16. The glass structural member according to any one of claims 1 to 15, characterized in that: The nanoindentation hardness of a side of the glass structure (100) away from the glass substrate (10) is greater than 14 GPa at an indentation depth greater than 150 nm.
17. The glass structural member according to any one of claims 1 to 16, characterized in that: The average transmittance of the glass structural member (100) in the visible light region is above 88%.
18. The glass structural member according to any one of claims 1 to 17, characterized in that: The color coordinate offset value ΔE of the glass structure (100) compared to the glass substrate (10) is less than 1.
5.
19. An electronic device (1000), characterized in that: It comprises a housing assembled on the outside of the electronic device (1000) and a circuit board located inside the housing, wherein the housing comprises the glass structural member (100) according to any one of claims 1 to 18.
20. The electronic device according to claim 19, characterized in that: The housing comprises a display screen cover plate (101) assembled on the front side of the electronic device (1000) and a back cover 102 assembled on the back side of the electronic device (1000); wherein the display screen cover plate (101) and / or the back cover (102) adopt the glass structural member (100).
21. The electronic device according to claim 19 or 20, characterized in that: The electronic device (1000) further comprises a camera assembly (2) located inside the housing, the housing comprising a camera protection cover (103), the camera protection cover (103) covering the camera assembly (2), the camera protection cover (103) using the glass structural member (100).
Citation Information
Patent Citations
Composite substrate structure and touch panel with same
CN104881163A
A high-hardness wear-resistant glass cover plate and a preparing method thereof
CN107746186A
Electronic equipment and shell thereof
CN116648014A
Glass apron and touch -sensitive screen
CN206201591U
Colour-neutral wear-resistant coating, substrate with such a neutral wear-resistant coating and process for producing the same
EP4011847A1
Cited By
Optical film and application thereof
CN122018055A
Glass structural member and electronic device
WO2026097897A1